Prevalência e fatores sociodemográficos associados à utilização das PICS no Brasil nos anos de 2013 e 2019 - Patrícia Paula Dias de Sá (2023)
Integrative and Complementary Practices (ICPs) consist of practices that seek to stimulate natural mechanisms to prevent illnesses and recover health through safe actions and the use of natural resources in health care, refusing to use substances that do not exist in nature, differentiating them from the biomedical model and medicalization, such as medicinal plants and herbal medicine, acupuncture, and homeopathy. Consequently, in 2006, the National Policy for Integrative and Complementary Practices (NPICP) was created with the aim of preventing illnesses, promoting and recovering health, and aimed at providing more humanized and comprehensive care, which currently encompasses 29 practices. This study aims to describe the prevalence and sociodemographic factors associated with the use of Integrative and Complementary Health Practices in Brazil. This is a cross-sectional study, using data from the National Health Surveys with a total sample of 64,348 and 108,525 households, in 2013 and 2019, respectively. The outcome of the study was the use of Integrative and Complementary Practices in 2013 and 2019. The explanatory variables were: macroregions of residence in the country (North, Northeast, Midwest, South, Southeast), gender (female or male), area (urban or rural), age (18-19, 20-24, 25-59 and 60 years or older), self-reported skin color/race (white, black, yellow or indigenous), marital status (married, divorced, widowed or single), education (elementary school, high school or higher education), and having health insurance (yes or no). The variables were also described as to whether the treatment was provided by the UHS (yes or no) and the types of ICPs used. Pearson's chi-squared test was used to assess possible associations, considering a significance level of 5%. To characterize the use of ICPs in 2013 and 2019, according to the different profiles of the interviewees, the decision tree method using the CART algorithm was used. The results showed that, in 2013, the largest proportion of practitioners was concentrated in the northern region of Brazil, and in 2019, in addition to this region, the northeast region was included. As for the explanatory variables, the profile of practitioners was as follows: female for both years (2013: 5.29%) (2019: 6.95%); age over 60 for both years (2013: 5.37%) (2019: 6.61%); rural area (2013: 6.82%), and urban area (2019: 5.66%); higher education level for both years (2013: 14.68%) (2019: 11.56%); marital status - widowed (2013: 5.51%), and marital status - divorced (2019: 7.42%); and indigenous ethnicity for both years (2013: 10.14%) (2019: 8.50%). In 2013, 6.40% of individuals received treatment through the UHS, and, in 2019, 6.52%. The most commonly used types of ICPs were: Acupuncture (2013: 22.23%) (2019: 27.96%); Homeopathy (2013: 13.02%) (2019: 17.94%); Medicinal Plants and Phytotherapy (2013: 59.04%) (2019: 56.53%); and others (2013: 5.7%) (2019: 5.3%). Despite the increase in the number of practitioners between 2013 and 2019, there is an undoubted need for greater participation by public managers in public health policies aimed at broad dissemination, legitimization, implementation, and monitoring of the National Policy for Integrative and Complementary Practices (NPICP). Similarly, it is essential that the Ministry of Health and the Ministry of Education promote research, investigation, and reflection on Integrative and Complementary Practices and their possible benefits to the Brazilian population's health.